Discretionary Grants and Distributive Politics: Evidence from Spain - Elena Jarocinska (Comparative Economic Studies, 2022)
We study empirically whether the allocation of discretionary grants across Spanish regions is related to the number of swing voters and loyal voters of the ruling party. We estimate the number of swing and loyal voters from survey data. When estimating the number of swing voters, we account in a novel way for the two-dimensional ideological space and multiparty competition. We find that regions with more loyal voters of the ruling party received more grants per capita. Partisan alignment of regional governments also matters over a part of the studied period since the regions where the socialist party of the central government was a member of the regional government received more grants.
Keywords: H5; H77; O1; 330; Distributive politics; Discretionary grants; Swing voters; Loyal voters; Partisan alignment; Spain